2015
DOI: 10.1007/s13277-015-4150-3
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-92a promotes growth, metastasis, and chemoresistance in non-small cell lung cancer cells by targeting PTEN

Abstract: MicroRNA-92a (miR-92a) has been reported to play important roles in tumorigenesis of human various cancers. However, the roles and underlying molecular mechanism of miR-92a in non-small cell lung cancer (NSCLC) have not been totally elucidated. Therefore, the aims of this study were to determine the role of miR-92a and to elucidate its regulatory mechanism in NSCLC. We found that miR-92a was significantly upregulated in NSCLC tissues compared to matched adjacent normal lung tissues, and its expression is signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 44 publications
6
51
0
Order By: Relevance
“…miR-92a-3p was evaluated as a diagnostic biomarker in CRC in previous study [14, 38, 39]. As a member of large cluster miR-17-92, miR-92a-3p has an important role as an oncogene in some cancers [40, 41]. Upregulation of the miR-92a-3p has been shown to disrupt the functions of several important factors of growth and division in colorectal cells [42].…”
Section: Discussionmentioning
confidence: 99%
“…miR-92a-3p was evaluated as a diagnostic biomarker in CRC in previous study [14, 38, 39]. As a member of large cluster miR-17-92, miR-92a-3p has an important role as an oncogene in some cancers [40, 41]. Upregulation of the miR-92a-3p has been shown to disrupt the functions of several important factors of growth and division in colorectal cells [42].…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, it was observed that overexpression of miR-92a-3p can disrupt PI3K/Akt/mTOR pathway by targeting two negative regulatory factors of this pathway, PTEN and PHLPP [29, 31]. Different studies have reported that overexpression of miR-92a-3p is involved in the development of metastasis and correlates with survival in different malignancies [3234].…”
Section: Discussionmentioning
confidence: 99%
“…PTEN may regulate PI3K signaling by dephosphorylating the lipid signaling intermediate phosphatidylinositol (3,4,5)-trisphosphate, and a clear link between the PI3K pathway and cancer was established in the 1980s (32). miRNA always operated by binding to the 3'UTRs of their target genes and a number of previous reports have confirmed that miR-106b serves its part in colorectal cancer, gastric cancer and hepatocellular carcinoma (33,34). In the present study, it was demonstrated that miR-106b inhibition may result in the increased expression of PTEN in ESCC cells compared with those in control cells.…”
Section: Downregulation Of Pten Partially Rescued the Induction Of Thmentioning
confidence: 99%